2008
DOI: 10.1086/593066
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Placental Malaria and HIV Infection on the Antibody Responses toPlasmodium falciparumin Infants

Abstract: Infant HIV infection and maternal coinfection with HIV and PM negatively influence antibody responses to TT, but not those to malarial antigens, in infants. Antimalarial antibodies rarely showed protective associations with morbidity in infants and were more often a marker for malaria exposure and risk of infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
19
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 40 publications
4
19
0
Order By: Relevance
“…Indeed, in the crude analysis, a common finding was that high antibody levels were associated with an increased risk of malaria. In another study in Manhiça, high maternal and fetal IgG levels were associated with a higher risk of malaria in the infant (49), and this was consistent with the findings of other similar studies (30,43). Nevertheless, when the analyses were adjusted for prior malaria episodes, the association disappeared, indicating that the main risk factor was the occurrence of previous episodes and that the antibodies were mere markers of the prior exposure.…”
Section: Discussionsupporting
confidence: 85%
“…Indeed, in the crude analysis, a common finding was that high antibody levels were associated with an increased risk of malaria. In another study in Manhiça, high maternal and fetal IgG levels were associated with a higher risk of malaria in the infant (49), and this was consistent with the findings of other similar studies (30,43). Nevertheless, when the analyses were adjusted for prior malaria episodes, the association disappeared, indicating that the main risk factor was the occurrence of previous episodes and that the antibodies were mere markers of the prior exposure.…”
Section: Discussionsupporting
confidence: 85%
“…Similarly, the decrease in transplacental IgGs in newborns did not increase their risk for clinical malaria during the first year of life. On the contrary, maternal and cord IgG levels were found to be associated with an increased risk of malaria in offspring, as it had been previously suggested in similar studies [37,38]. It could be argued that high antibody levels in pregnant women reflect maternal infection and, thus, an increased risk of fetal exposure to P. falciparum antigens, which may lead to enhanced malaria susceptibility in the offspring [39,40].…”
Section: Discussionmentioning
confidence: 60%
“…7,25,26,3032,35,36,40 Thirteen studies compared proportions of anemia between those who were co-infected and those who had monoinfected. 22,24,2729,33,34,3739,4143 Anemia was comparable between the monoinfected and co-infected adults (summary OR: 1.49, 95% CI: 0.93–2.37) and increased by 49% in co-infected pregnant women (summary OR: 1.49, 95% CI: 1.14–1.94) (Figure 3). Only 1 study on children reported that anemia was 5.5 times more in the co-infected group.…”
Section: Resultsmentioning
confidence: 96%
“…Among these, 13 studies reported prevalence of HIV in malaria-infected patients, 2224,27,28,30,35,3740,42,43 whereas 10 studies on prevalence of malaria in HIV positives. 7,25,26,29,31–34,36,41 …”
Section: Resultsmentioning
confidence: 99%